Poverty in Albania : A Qualitative Assessment - De Soto, Hermine; Gordon, Peter; Gedeshi, Ilir; Sinoimeri, Zamira (Washington, DC: World Bank, 2013)
This qualitative assessment of poverty in Albania seeks to deepen the understanding of poverty in the country, first, by involving poor Albanians in a process of exploring the causes, nature, extent of poverty, and how it affects their livelihoods. Second, it is intended to support the Growth and Poverty Reduction Strategy Paper (PRSP). Third, it supports preparation of the Country Assistance Strategy (CAS), and the Living Standards Measurement Survey (LSMS) process. Fourth, it supports ongoing research on formal and informal institutions in the country that are relevant to poverty, and it identifies as well, emerging areas of concern. Findings suggest that poverty in the study sites, developed as a result of a weak economic base at the beginning of reform (as of 1990), worsened as the reforms continued and accelerated during the 1997 financial crisis. From household interviews, it is perceived that the causes of poverty are a result of unemployment, insufficient and low quality of land, absence of formal institutions, and marketing mechanisms to support industrial and agricultural development, and the government's inability to respond to infrastructure and basic needs. The study further examines the factors depressing and/or precluding (sector wide) the potential to compete, sustain livelihoods, attain employment, and receive economic and social assistance.